THE USE OF MATH COUNTING BOARDS IN IMPROVING EARLY COUNTING SKILLS IN CHILDREN AGED 5-6 YEARS - Khofifah, Khofifah; Zulkarnaen, Zulkarnaen (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
Currently, there are still many children who have difficulty learning to count. So, learning media that is interesting and not monotonous is needed in order to develop student interest and improve students' ability to calculate. This research aims to describe 1) Implementation of the use of a mathematical calculation board. 2) obstacles and challenges in using mathematical calculation boards. 3) Teacher perceptions of the effectiveness of the mathematics calculation board. This research uses a qualitative descriptive research method with a case study approach. This research was carried out at Siwi Peni Grobogan Kindergarten with subjects including Siwi Peni Kindergarten students aged 5-6 years with a total of 15 students and teachers participating, namely the Siwi Peni Kindergarten homeroom teacher, and also the principal of Siwi Peni Kindergarten. The data collection techniques used were interviews, observation and documentation.  The data analysis used is the Miles and Huberman theory, namely data collection, data reduction, and drawing conclusions. Based on the research results, it can be stated that: 1) The use of counting board media is carried out through three stages, namely the planning stage, implementation stage and evaluation stage. 2) Obstacles and obstacles in using counting board media, namely the teacher's lack of knowledge regarding learning media, lack of facilities and infrastructure, and students not knowing how to write numbers, which hinders learning activities.  3) Based on the teacher's perception of the effectiveness of using counting board media, it can be said to be effective, because it is able to increase student involvement in class and improve students' numeracy skills..